The Strategic Value of Carbon Tariffs - Christoph Böhringer; Jared C. Carbone; Thomas F. Rutherford (University of Oldenburg, Department of Economics, 2014)
Unilateral carbon policies are inefficient due to the fact that they generally involve emission reductions in countries with high marginal abatement costs and because they are subject to carbon leakage. In this paper, we ask whether the use of carbon tariffstariffs on the carbon embodied in imported goodsmight lower the cost of achieving a given reduction in world emissions. Specifically, we explore the role tariffs might play as an inducement to unregulated countries adopting emission controls of their own. We use an applied general equilibrium model to generate the payoffs of a policy game. In the game, a coalition of countries regulates its own emissions and chooses whether or not to employ carbon tariffs against unregulated countries. Unregulated countries may respond by adopting emission regulations of their own, retaliating against the carbon tariffs by engaging in a trade war, or by pursuing no policy at all. In the unique Nash equilibrium produced by this game, the use of carbon tariffs by coalition countries is credible. China and Russia respond by adopting binding abatement targets to avoid being subjected to them. Other unregulated countries retaliate. Cooperation by China and Russia lowers the global welfare cost of achieving a 10% reduction in global emissions by half relative to the case where coalition countries undertake all of this abatement on their own.
Keywords: 330; Ökosteuer; Import; Immissionsschutz; Internationale Umweltpolitik; Nash-Gleichgewicht; Allgemeines Gleichgewicht; Spieltheorie